Advancing construction safety: A hybrid construction safety risk index and kernel density estimation approach for assessing construction safety risks. - Ahmadi, Fatemeh; Sadeghi-Yarandi, Mohsen; Ghiyasi, Samira; Mousavi, Mohammadreza; Soltanzadeh, Ahmad (Work, 2026)
Background: The construction industry is vital for employment, making productivity and safety improvements crucial. Objective: To address the persistent lack of integrated spatial and quantitative construction risk assessments, this study introduces a novel hybrid approach that merges the Construction Safety Risk Index with Kernel Density Estimation. This methodology fills an essential research gap in proactive construction risk management. Method: This study was conducted during the 2023–2024 period within a large construction project. The study employed the CSRI technique and the KDE method. To implement this study, an information plan related to each section, along with an item description table and a probability and severity index table, was provided to the experts. By completing the item description table, the CSRI number for each item was determined. Ultimately, the output from the Kernel tool produced accident risk maps for each floor. Results: The results indicate that most locations, including openings, electrical cables, electrical panels, gas lines, elevator shafts, and tower movement areas, were categorized within the yellow zones, which fall within the tolerable range. Approximately 62% of risk-prone zones were classified as yellow (tolerable). However, in certain areas, high-risk items interact with one another, resulting in some points on the map being marked in red. More than 85% of recorded incidents matched predicted red zones. Conclusion: This study successfully integrates the CSRI and KDE to spatially assess construction risks. Most hazards fall within tolerable zones, while high-risk interactions create critical hotspots. The hybrid approach enhances proactive risk management, enabling targeted safety interventions.